Presidentes y orquestadores: la gobernanza de la pandemia de Covid-19 en las Américas - Legler, Thomas (El Colegio de México A.C., 2021)
This article seeks to interpret and explain contradictory trends in the hemispheric and regional governance of the Covid-19 pandemic. Based on an extensive mapping exercise of cooperation and institutional trends, this article depicts a mix of conflicting governance tendencies, both negative and positive, as well as disarticulated and collaborative. The author argues that the existing governance of the pandemic in the hemisphere stems from the historical convergence and intertwining of two macro governance patterns in health security in recent decades: inter-presidentialism and orchestration by regional organizations. Despite the impression of individualized national responses and governance dysfunctionality, a veritable effervescence of heterogeneous hemispheric and regional forms of cooperation and institution-building has occurred against the virus and its broader fallout. Thanks to their resilience and organizational capacity, various formal regional organizations and development banks managed to offset at least partially disturbing trends in pathological inter-presidentialism through their roles as governance orchestrators. On the basis of its findings, the article calls for theoretical cross-fertilization among comparative regionalism, neoliberal institutionalism, and global governance studies, as well the construction of networked inter-presidentialism in order to counterbalance the worst impulses of presidents.